Bibliography of Ethiopian Semitic, Cushitic and Omotic Linguistics XX: 2016 - Bulakh, Maria; Hummel, Susanne; Panini, Francesca (Aethiopica, 2017)
Bibliography of Ethiopian Semitic, Cushitic and Omotic Linguistics XX: 2016